2022
DOI: 10.1002/gps.5697
|View full text |Cite
|
Sign up to set email alerts
|

Time trends in psychotropic drug prescriptions in Dutch nursing home residents with dementia between 2003 and 2018

Abstract: Objective Several European studies investigated the trends in psychotropic drug prescriptions (PDPs) among nursing home (NH) residents and reported a decline in antipsychotics prescriptions. Since the Dutch long‐term care system differs from other European systems (e.g. higher threshold for NH admission and trained elderly care physicians), this study explores the trends in PDPs in Dutch NH residents with dementia. Methods The study used data from nine studies, comprising two cross‐sectional studies, one cohor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…In Canada, an online public reporting initiative was associated with a 6% reduction in antipsychotic use in nursing homes over a 3 year period 9 . A similar decreasing antipsychotic trend was reported in nursing homes in several European countries, including Sweden and the Netherlands 10,11 . While applauding these efforts, several authors of these studies warned about the potential unintended consequences of targeting antipsychotics, including psychotropic substitutions involving an increase in the use of non‐antipsychotic off‐label prescriptions with similar risks of harm 9,12 …”
Section: Figurementioning
confidence: 89%
See 3 more Smart Citations
“…In Canada, an online public reporting initiative was associated with a 6% reduction in antipsychotic use in nursing homes over a 3 year period 9 . A similar decreasing antipsychotic trend was reported in nursing homes in several European countries, including Sweden and the Netherlands 10,11 . While applauding these efforts, several authors of these studies warned about the potential unintended consequences of targeting antipsychotics, including psychotropic substitutions involving an increase in the use of non‐antipsychotic off‐label prescriptions with similar risks of harm 9,12 …”
Section: Figurementioning
confidence: 89%
“…The American Geriatrics Society's Choosing Wisely Guidelines likewise recommends that antipsychotics should not be used as the first choice to treat BPSD 7 . These warnings and guidelines accompanied increased public attention as well as campaigns using audit, feedback and reporting which resulted in decreased antipsychotic use among nursing home residents in several countries 8–11 . Two US studies have demonstrated a decrease in antipsychotic prescribing from 33.7% to 27.5% between 2009 and 2018, 8 and from 32.1% to 27.9% between 2015 and 2019 1 .…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Decreased use of antipsychotics has been observed in studies conducted in PRAC facilities in the United States and Netherlands, 43,44 but not the United Kingdom. 45 The 3% annual decrease in prolonged use observed in our study likely reflects changes to the product information for risperidone 21 and large-scale policy and quality improvement initiatives 46 diagnosis coding 52 which may also need to be monitored if the CQI tested in our study is implemented.…”
Section: Discussionmentioning
confidence: 99%